Graph-theoretic concepts in computer science : 44th International Workshop, WG 2018, Cottbus, Germany, June 27-29, 2018, Proceedings /: 44th International Workshop, WG 2018, Cottbus, Germany, June 27-29, 2018, Proceedings. (2018) - Unknown
No abstract available